53Mn and 60Fe in iron meteorites—New data, model calculations. (31st March 2020) - Leya, Ingo; David, Jean‐Christophe; Faestermann, Thomas; Froehlich, Michaela; Kivel, Niko; Koll, Dominik; Korschinek, Gunther; McIntyre, Sarah; Merchel, Silke; Pavetich, Stefan; Rugel, Georg; Schumann, Dorothea; et al.
Abstract: We measured specific activities of the long‐lived cosmogenic radionuclides 60 Fe in 28 iron meteorites and 53 Mn in 41 iron meteorites. Accelerator mass spectrometry was applied at the 14 MV Heavy Ion Accelerator Facility at ANU Canberra for all samples except for two which were measured at the Maier‐Leibnitz Laboratory, Munich. For the large iron meteorite Twannberg (IIG), we measured six samples for 53 Mn. This work doubles the number of existing individual 60 Fe data and quadruples the number of iron meteorites studied for 60 Fe. We also significantly extended the entire 53 Mn database for iron meteorites. The 53 Mn data for the iron meteorite Twannberg vary by more than a factor of 30, indicating a significant shielding dependency. In addition, we performed new model calculations for the production of 60 Fe and 53 Mn in iron meteorites. While the new model is based on the same particle spectra as the earlier model, we no longer use experimental cross sections but instead use cross sections that were calculated using the latest version of the nuclear model code INCL. The new model predictions differ substantially from results obtained with the previous model. Predictions for the 60 Fe activity concentrations are about a factor of 2 higher, for 53 Mn, they are ~30% lower, compared to the earlier model, which gives now a better agreement with the experimental data.